Beware of Popular Kids Bearing Gifts: A Framed Field Experiment - Jingnan Chen; Daniel Houser; Natalia Montinari; Marco Piovesan (Lund University, School of Economics and Management, Department of Economics, 2014)
The literature on pro-social behavior shows that older children are more generous than younger children; however, the level of individual generosity is heterogeneous even between children of the same age. This paper investigates whether a child's popularity affects a child's generosity. Our participants – 231 children, six to twelve years old – decide how many of their four colored wristbands they want to share with another anonymous child. We manipulate the visibility of this decision: in treatment Public, the decisions are revealed to the entire class at the end of the game, whereas in treatment Private children's decisions remain secret. In addition, we elicited each child's network of friends using an innovative "seating map" mechanism. Our results reveal that more popular children are more generous in Public than Private decision environments, while less popular children behave similarly in both cases. Moreover, older children in Public display greater generosity than (i) older children in Private and (ii) younger children in either Public or Private. Finally, in Public, older and more popular children share more than less popular older children, and more than younger children regardless of popularity; whereas, in Private there is no effect of popularity on children of any age.
Keywords: C93; J13; 330; popularity; children; field experiment; public decision making; pro-social behavior